TINJAUAN SOSIAL EKONOMI PEKERJA ANAK DI BAWAH USIA KERJA - Sri Astiti, Ni Wayan (Jurnal Studi Jender SRIKANDI, 2012)
This study aims to understand about social economic of underage workers at Taman Bali village, Bangli Regency. The result of this research shows that the age of the underage workers is from 11 until 14 years old. They work at handicraft and printing industries. They work about 3.41 hours a day after schooling and earn about Rp.2.450 a day. They spend their earning for fulfilling their own need, paying tuition, or giving it to their parents. They work because they want to help their parents, want to get own money, to spend their spare time and to learn skills on handicraft and printing. Their parents support their activities because during their children work they will be able to stand alone, learn to save money and help their parents to fulfill daily needs. This research also find that the socialization of the regulation of Manpower has never done in this place, so that it is very important to socialize the rules to the village in order to give the village comprehending about their rights and duties as workers.
Keywords: Pekerja Anak, Sosial Ekonomi